Deposit competition, interbank market, and bank profit - Bo Jiang; Hector Tzavellas; Xiaoying Yang (Journal of Risk and Financial Management, 2022)
In this paper, we study how the interbank market could impact deposit competition and bank profits. We first document two stylized facts: the net interbank funding ratio is negatively correlated with net interest margin (NIM), as well as with the cost-to-income ratio (CIR). To rationalize these two facts, we embed the interbank market into a BLP model framework. The model is calibrated using Chinese listed banks' data. A counterfactual experiment reveals that shutting down the interbank market will lead to a decline in NIM and bank profits. Our results indicate that the interbank market can facilitate specialization and reduce the intensity of deposit competition.
Keywords: 650; Bank Profitability; BLP; deposit competition; interbank market; structural estimation